FROM YOUTUBE TO TV, AND BACK AGAIN: VIRAL VIDEO CHILD STARS AND MEDIA FLOWS IN THE ERA OF SOCIAL MEDIA - Leaver, Tama; Abidin, Crystal (AoIR Selected Papers of Internet Research, 2018)
While talk shows and reality TV are often considered launching pads for ordinary people seeking to become celebrities, we argue that when children are concerned, especially when those children have had viral success on YouTube or other platforms, their subsequent appearance(s) on television highlight far more complex media flows. At the very least, these flows are increasingly symbiotic, where television networks harness preexisting viral interest online to bolster ratings. However, the networks might also be considered parasitic, exploiting viral children for ratings in a fashion they and their carers may not have been prepared for. In tracing the trajectory of Sophia Grace and Rosie from viral success to The Ellen Show we highlight these complexities, whilst simultaneously raising concerns about the long-term impact of these trajectories on the children being made increasingly and inescapably visible across a range of networks and platforms.